Calcium to Magnesium Ratio Higher Than Optimal Across Age Groups (P10-100-19). (13th June 2019) - DeLuccia, Rosemary; Cheung, May; Ng, Tammy; Ramadoss, Rohit; Altasan, Asma; Sukumar, Deeptha
Abstract: Objectives: The ratio of calcium to magnesium (Ca: Mg) intake has gained immense attention in recent years, since a ratio above 2:1 has been associated with increased risk of metabolic, inflammatory and cardiovascular disorders. The objective of this study was to assess Ca: Mg ratios across age groups and to determine the relationship between Ca: Mg ratios and markers of inflammation. Methods: Adult men and women, 18 to 60 years of age, completed a demographic form, a magnesium food frequency questionnaire and a calcium food frequency questionnaire. In a subset of individuals, biochemical assays were completed for inflammation markers such as interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), C-reactive protein (CRP) and matrix metallopeptidase 9 (MMP-9). Means, standard deviations, medians and interquartile ranges were calculated, and Pearson's correlations were conducted to determine the relationship between Ca: Mg ratio and markers of inflammation. Results: Fifty-six adults were included in this analysis, and were categorized into four age categories: 18 to 29 years, 30 to 39 years, 40 to 49 years and 50 to 59 years. On average, participants were 28.87 ± 10.16 years of age, with a body mass index of 24.54 ± 3.72 kg/m 2 . Mean magnesium intake, calcium intake and Ca: Mg ratio for each age group were: 249.08 mg, 763.89 mg and 3.37 for the 18–29 years group, 226.59 mg, 730.50 mg and 3.58 for the 30 to 39 years group, 252.63 mg, 731.29 mg and 3.19 for the 40 to 49 years group and 286.03 mg, 595.03 mg and 2.79 mg for the 50 to 59 years group. All study groups had lower magnesium and calcium intakes compared to the Recommended Daily Allowances for these nutrients; however, the Ca: Mg ratio was higher than the optimal ratio of 2:1 in all age groups. In a subset, Ca: Mg ratio was significantly associated with IL-6 (r = 0.626, P  = 0.017). Conclusions: All age groups had a high Ca: Mg ratio above the optimal 2:1 ratio and in a subset of participants, a higher Ca: Mg ratio was associated with greater inflammation. Interventional studies should target lowering the Ca: Mg ratio in the diet and assess the effect of lowering Ca: Mg ratio on changes in metabolic markers. Funding Sources: None.